2001
DOI: 10.1002/app.1371
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of block copolymers of poly(ε‐caprolactone) and poly(ethylene glycol) with poly(3‐hydroxybutyrate) as well as the compatibilizing effect of these copolymers in blends of poly(ε‐caprolactone) and poly(3‐hydroxybutyrate)

Abstract: Atactic poly(3-hydroxybutyrate) (a-PHB) and block copolymers of poly(ethylene glycol) (PEG) with poly(-caprolactone) (PCL-b-PEG) were synthesized through anionic polymerization and coordination polymerization, respectively. As demonstrated by differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) measurements, both chemosynthesized a-PHB and biosynthesized isotactic PHB (i-PHB) are miscible with the PEG segment phase of PCL-b-PEGs. However, there is no evidence showing miscibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Since natural rubber is completely amorphous, the only explanation of this behavior is that some PHB crystallites were affected by the rubber to form a different type of crystal due to some interaction between them. 29 When there are two types of crystals, it is possible for them to have different melting points. The DSC curves were also used to obtain the melting enthalpies of the PHB phases in the virgin polymer and the blend.…”
Section: Resultsmentioning
confidence: 99%
“…Since natural rubber is completely amorphous, the only explanation of this behavior is that some PHB crystallites were affected by the rubber to form a different type of crystal due to some interaction between them. 29 When there are two types of crystals, it is possible for them to have different melting points. The DSC curves were also used to obtain the melting enthalpies of the PHB phases in the virgin polymer and the blend.…”
Section: Resultsmentioning
confidence: 99%
“…The compatibilized blend was more hydrophilic than the uncompatibilized one. Shuai et al25 reported that the PEG segments in PEG‐PCL or PCL‐PEG‐PCL were miscible with another aliphatic polyester, poly(3‐hydroxybutyrate) (PHB), while the PCL segments of the copolymers are immiscible with PHB. On the basis of these results, PCL/PEG block copolymers were added as a compatibilizer to PCL/PHB blends.…”
Section: Discussionmentioning
confidence: 99%
“…The compatiblization of PLA/PCL blend with PCL‐ b ‐PEG copolymer showed improvement in mechanical performances. Similarly, PCL‐ b ‐PEG copolymer has been used as a compatibilizer in PCL/PHB blends to improve the compatibility . Choi et al .…”
Section: Principle and Mechanism Of Ex Situ Compatibilization Of Polymentioning
confidence: 99%